Pascal for BASIC programmers - Seiter, Charles (Massachussets : Addision-Wesley Publishing Company, 1983)
BASIC and Pascal are both computer languages that have been adapted elegantly to microcomputers. Although they are similar in many details, the flavor of programming in them is quite different. Each has its strengths and its weaknesses. This book is oriented toward a reader who has a home or small business computer, is familiar with BASIC, and wants to investigate the power and convenience of Pascal. It should also be useful to a BASIC programmer encountering Pascal on a larger computer.